Graham Beasley

Answered question

2022-07-26

Use the rules of exponents to simplify each expression.
$\left({m}^{-3}{\right)}^{-1}\left({m}^{2}{\right)}^{-4}$

Answer & Explanation

Carassial3

Beginner2022-07-27Added 9 answers

$\left({m}^{-3}{\right)}^{-1}\left({m}^{2}{\right)}^{-4}=\left(\frac{1}{{m}^{3}}\right)\left(\frac{1}{{m}^{2}}{\right)}^{4}$
$={m}^{3}×\left(\frac{1}{{m}^{8}}\right)$
$=\frac{{m}^{3}}{{m}^{8}}=$ since it's division you have to subtractthe powers
$={m}^{3-8=-5}$
$={m}^{-5}=\frac{1}{{m}^{5}}$ answer.

Joanna Mueller

Beginner2022-07-28Added 5 answers

multiply Exponents
${m}^{3}\left(1/{m}^{8}\right)$ all negatives to make positiveuse recipacol ${n}^{-2}=1/{n}^{2}$
${m}^{-3}$ here we simplified the division my subtraction
$1/{m}^{5}$ and once again we use the rule two lines above

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?